EFFECTIVENESS OF GROUP-MEDIATED LIFESTYLE PHYSICAL ACTIVITY (GLPA) PROGRAM FOR HEALTH BENEFIT IN PHYSICAL ACTIVITY AMONG ELDERLY PEOPLE AT RURAL THAILAND - Ethisan, Plernta; Chapman, Robert; Kumar, Ramesh; Somrogthong, Ratana (Journal of Ayub Medical College Abbottabad, 2015)
Background: Elderly population is considered as a vulnerable group and prone to develop multiple medical problems. This aging population is rapidly increasing in developing countries especially in Thailand. Methods: This study was a quasi-experimental study to evaluate the effectiveness of Group-Mediated Lifestyle Physical Activity program on change health benefit in physical activity among elderly people by using validated and reliable Global Physical Activity Questionnaire-GPAQv2. The study was conducted in Phranakhonsiayutthaya district, Ayutthaya province due to its population being the second highest elderly in the Central Region of Thailand. A total of 102 persons of age 60 and over who could read and write Thai language were selected purposively. However, 52 elderly were enrolled in the intervention group and 50 were enrolled for the control group. General Linear Model repeated-measures ANOVA was used to evaluate the effects of Group-Mediated Lifestyle Physical Activity (GLPA) program on change health benefit in physical activity among elderly. Results: Overall health benefit at baseline were similar between intervention and control group and found statistically non-significant with p-value 0.638 (>0.05). However, the mean score of health benefit was 23.21±29.23 in intervention group and 20.74±23.18 in control group. One third of participants of intervention group had not found health benefit due to physical activity while in control group this number was more than half. After elderly received Group-Mediated Lifestyle Physical Activity program intervention for 6 month found significant statistical differences as compared with mean score at baseline (health benefit 6 month, intervention group =40.7±34.28 and control group =4.56±8.79). Conclusion: The effect of Group-Mediated Lifestyle Physical Activity program change intervention was statistically significant in health benefit after intervention program between intervention and control group. Our study suggested that there was need of promoting and encourages physical activity to increase health benefit among elderly people in rural area. Keyword: elderly, health benefit, physical activities